Polymer actuators based on covalent adaptable networks. Issue 33 (20th May 2020) - Wu, Yahe; Wei, Yen; Ji, Yan
Abstract : Advances in polymer actuators containing covalent adaptable networks (CANs) are summarized and discussed in this review. Abstract : The combination of dynamic covalent chemistry (DCC) with polymeric materials has sparked numerous innovations over the past two decades. One outstanding branch is the application in polymer actuators. Substantial progress has been made in this area regarding novel stimuli-responsive functions, such as intriguing responsiveness, reprogrammable functions, recyclability, and self-healability, more efficient actuator fabrication, new advanced actuation systems, etc . Through reasonable system design and function matching, different DCC strategies have been continuously discovered and employed, creating a variety of polymer actuators with covalent adaptable networks (CANs), which have been smashing the stereotypes of the materials that have already been studied for several decades such as shape memory polymers (SMPs) and liquid crystalline elastomers (LCEs). This review aims to overview the strategies for building polymer actuators based on CANs, how they function, and the advances induced by the introduction of CANs. An outline of CANs, DCC and the strategies on network design will be given at first. Further, we summarize the essential impacts inaugurated by CANs in different kinds of polymer actuators and shape the possible future directions in this sustainably growing field.